No evidence that sex and transposable elements drive genome size variation in evening primroses. (1st April 2015) - Ågren, J. Arvid; Greiner, Stephan; Johnson, Marc T. J.; Wright, Stephen I.
Abstract: Genome size varies dramatically across species, but despite an abundance of attention there is little agreement on the relative contributions of selective and neutral processes in governing this variation. The rate of sex can potentially play an important role in genome size evolution because of its effect on the efficacy of selection and transmission of transposable elements (TEs). Here, we used a phylogenetic comparative approach and whole genome sequencing to investigate the contribution of sex and TE content to genome size variation in the evening primrose ( Oenothera ) genus. We determined genome size using flow cytometry for 30 species that vary in genetic system and find that variation in sexual/asexual reproduction cannot explain the almost twofold variation in genome size. Moreover, using whole genome sequences of three species of varying genome sizes and reproductive system, we found that genome size was not associated with TE abundance; instead the larger genomes had a higher abundance of simple sequence repeats. Although it has long been clear that sexual reproduction may affect various aspects of genome evolution in general and TE evolution in particular, it does not appear to have played a major role in genome size evolution in the evening primroses.